Analysis of the Menus' Factors that are Influential in Determining the Marketing Mix : an Empirical Study on Mawar Saron Restaurant in Puri Saron Hotel Seminyak - Bali - Sengkey, Fenny; Osin, Rosvita Flaviana (Jurnal Manajemen Pelayanan Hotel, 2023)
In the global tourism sector, food and beverage menus no longer play a supporting role. In contrast, food occupies a central position both in determining tourists' decision-making to travel and vacation experiences. The purpose of this study was to determine the level of popularity of the menu and the profit level of the menu at Mawar Saron Restaurant. In addition, this study also aims to determine what marketing strategies are appropriate to use to increase sales results according to the menu category. The data analysis technique used in this study is the engineering menu analysis technique which consists of 12 steps. The results of research on the Mawar Saron Restaurant in Puri Saron Seminyak can be seen that 32% or 16 menu items of the entire ala carte menu offered belong to the star menu class (popular and profitable), 26% or 13 menu items belong to the Plowhorse menu class (popular but unprofitable). ) and 20% or 10 menu items belong to the Puzzle menu class (less popular but profitable). While 22% or 11 menu items belong to the Dog menu class (less popular and less profitable). Management policies implemented in increasing food sales are maintaining food quality and price for the star group, increasing food quality and selling price of food for the plowhorse group, improving food raw materials so as to reduce food prices for the puzzle group and evaluating materials, services, promotions and food prices for the dog category. Keywords: Menu popularity, Food Cost, Margin Contribution